2019
DOI: 10.1097/aln.0000000000002882
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacodynamic Interaction of Remifentanil and Dexmedetomidine on Depth of Sedation and Tolerance of Laryngoscopy

Abstract: Background: Dexmedetomidine is a sedative with modest analgesic efficacy, whereas remifentanil is an opioid analgesic with modest sedative potency. Synergy is often observed when sedative-hypnotics are combined with opioid analgesics in anesthetic practice. A three-phase crossover trial was conducted to study the pharmacodynamic interaction between remifentanil and dexmedetomidine. Methods: After institutional review board approval, 30 age-and sex-stratified healthy volunteers were studied. The subjects receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 35 publications
0
42
0
1
Order By: Relevance
“…13 EEG data for propofol and sevoflurane were recorded using a 16-channel Neuroscan® EEG monitor (Compumedics Limited, Charlotte, NC, USA) in healthy volunteers with sampling frequency of 5 kHz, and were later reduced to 1 kHz during transition to extraction file. For dexmedetomidine, 14 a BrainAmp DC32 amplifier with a BrainVision recorder (Brain Vision Solutions, Montreal, Canada) was used to record the 17-channel EEG at a sampling rate of 5 kHz. In all groups, the volunteers were asked to keep their eyes closed for the entire study duration.…”
Section: Volunteer Selection and Data Collectionmentioning
confidence: 99%
“…13 EEG data for propofol and sevoflurane were recorded using a 16-channel Neuroscan® EEG monitor (Compumedics Limited, Charlotte, NC, USA) in healthy volunteers with sampling frequency of 5 kHz, and were later reduced to 1 kHz during transition to extraction file. For dexmedetomidine, 14 a BrainAmp DC32 amplifier with a BrainVision recorder (Brain Vision Solutions, Montreal, Canada) was used to record the 17-channel EEG at a sampling rate of 5 kHz. In all groups, the volunteers were asked to keep their eyes closed for the entire study duration.…”
Section: Volunteer Selection and Data Collectionmentioning
confidence: 99%
“…Remifentanil undergoes very high clearance independent of organ function and infusion duration [23], and this also explains why respiratory depression was not observed in this study. A recent study also concluded that the co-administration of remifentanil and DEX infusion did not influence the arousability during general anesthesia [24]. NRS scores at the first postoperative hour were lower in group D both at rest and at movement.…”
Section: Discussionmentioning
confidence: 85%
“…Research on the effects of remifentanil on PSI are scarce in the literature but it seems that remifentanil alone has a slight effect on the PSI [32]. They observed that PSI values decreased below the PSI baseline predicted by the model with no clear relationship between PSI and measured remifentanil concentrations.…”
Section: Discussionmentioning
confidence: 98%